Granted - Anderson, John David (Walden Pond Press, an imprint of HarperCollinsPublishers, 2018)
Young fairy Ophelia gets her first wish granting assignment and discovers that, although the fate of the fairy world rests on her completing her task, the job of granting a human's wish is anything but easy